2022
DOI: 10.1002/ps.7296
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of the yellow‐legged hornet (Vespa velutina) using an optical sensor with machine learning

Abstract: BACKGROUND: The yellow-legged hornet (Vespa velutina) is native to Southeast Asia and is an invasive alien species of concern in many countries. More effective management of populations of V. velutina could be achieved through more widespread and intensive monitoring in the field, however current methods are labor intensive and costly. To address this issue, we have assessed the performance of an optical sensor combined with a machine learning model to classify V. velutina and native wasps/hornets and bees. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Recently, research has been conducted on the automated detection of V. velutina using optical sensors with machine learning by analyzing the wingbeat frequencies of seven species of bees, wasps, and hornets. This research was carried out in an entomological tent in the laboratory, and V. velutina individuals were detected by distinguishing species of bees, wasps, and hornets based on the wingbeat frequency [32]. Previous studies have also used machine learning to predict the prioritization of tasks in sighting reports of V. velutina in situations in which human resources are limited [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has been conducted on the automated detection of V. velutina using optical sensors with machine learning by analyzing the wingbeat frequencies of seven species of bees, wasps, and hornets. This research was carried out in an entomological tent in the laboratory, and V. velutina individuals were detected by distinguishing species of bees, wasps, and hornets based on the wingbeat frequency [32]. Previous studies have also used machine learning to predict the prioritization of tasks in sighting reports of V. velutina in situations in which human resources are limited [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our technique is effective in performance and report measurements. Drawing upon an extensive review of relevant academic literature, a majority of the research conducted on images [28][29][30][31][32][33][34][35][36][37][38][39]50] indicates a lack of sufficient attention towards the establishment of reliable analytical techniques for prevention and control [40][41][42][43][44][45] and accurately identifying pests through the analysis of acoustic signals produced by these pests [46][47][48][49]. The summarized findings of these reviews can be found in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When considering the performance of current operational detection systems, these achieve mean classification accuracies within the range of ~74.5–83.3% for V. velutina 39 , 41 , but suffer from false detections of other hornet species 41 , and in some cases honey bees 39 , 42 . False positives therefore have the potential to accumulate rapidly over time, degrading the efficacy of such systems in cases where true positives are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of deep learning to this challenge is evident through parallel machine vision applications in behavioural tracking [28][29][30][31] , pest management [32][33][34] , and conservation biology [35][36][37] . Consequently, there have been several attempts to develop proof-of-concept detection systems for various Vespa species-primarily utilising optical [38][39][40][41] , infrared 42 , and acoustic sensors 43 . These efforts have yielded prototype monitors for deployment at apiaries, with initial tests successfully detecting the presence of hornets in real-time 39,42 .…”
mentioning
confidence: 99%